The effect of primary dealer constraints on intermediation in the treasury market - Falk Bräuning; Hillary Stein (Federal Reserve Bank of Boston, 2024)
Using confidential microdata, we show that shocks to primary dealers' risk-bearing constraints have significant effects on the US Treasury securities market. In response to tighter constraints, dealers reduce their Treasury positions, triggering a reduction in aggregate turnover and an increase in bid-ask spreads. These effects are more pronounced in securities that contribute more to the utilization of risk constraints. The impaired intermediation also affects Treasury yields, amplifying the yield response to net demand shifts. Moreover, tighter dealer constraints weaken Treasury auction outcomes: Bid-to-cover ratios decline, driven by dealers' less aggressive bidding, and the highest yield accepted by participants rises, thereby increasing the government's cost of issuing debt. Using our estimates, we back out key elasticities to show that the shadow cost of dealer constraints is as high as one-third of dealers' intermediation margin.
Keywords: G10; G12; G18; G21; 330; Treasury market; primary dealers; intermediation; risk constraints